Trauma-informed care for everyone: A study on patient and provider perspectives in an urban primary care setting - Jannah M. Wigle; Clara Juando-Prats; Andree Schuler; Katie Sussman; Alyssa Swartz; Chantal Sorhaindo; Seema Bhandarkar; William Watson; Allison Farber (PLoS ONE, 2026)
Background The importance of trauma-informed care is increasingly acknowledged as essential to generating a trusted relationship and safe environment in which to mitigate harms or effects of seeking health services by both patient and primary health care providers. Despite established models and principles of trauma-informed care, in practice there is limited research on the implementation of trauma-informed care within interdisciplinary primary care settings. Methods This research was conducted at a multi-site interdisciplinary primary health care team in Toronto, Canada. Guided by an interpretative qualitative and patient-oriented methodological approach, we conducted semi-structured interviews with 10 patients and 13 primary care providers from January 2023 to March 2024. Results Patients and primary health care providers conceptualized trauma-informed care as a holistic, patient-centred approach that is foundational to delivering quality, primary health care. Ensuring that primary health care is universally trauma-informed was perceived by all participants as essential to better understanding patients’ health, care-seeking, and health system experiences. Primary care providers are uniquely positioned to integrate trauma-informed care into clinical practices given sustained relationships and trust with patients. The availability and accessibility of trauma-specific supports and underlying contextual factors also inherently shaped the lived experiences of obtaining or delivering care among patients and providers. Conclusions A paradigmatic shift towards a more holistic and person-centred approach is fundamental to integrating trauma awareness and precautions in primary care and the health system. Overcoming obstacles that circumscribe the availability and accessibility of trauma-informed care and trauma-specific resources is paramount to promoting health, mental health, and health equity.